Desain Interaksi Game Edukasi Pawzle Care untuk Pecinta Kucing (Ailurophile) dengan Menggunakan Pendekatan Participatory Design - Finandhita, Alif; Octaviane, Yolanda; Dharmayanti, Dian (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2025)
This research aims to develop an effective interaction design model for educational games tailored for cat enthusiasts (ailurophiles). Cats hold a special place in our hearts, and their well-being, including proper care, health maintenance, and development monitoring, is of utmost importance. However, as revealed by the questionnaire, there is a gap in knowledge among cat lovers regarding essential care techniques. These techniques encompass equipment selection, cat care procedures, and crucial information about our feline companions. To achieve our research objectives, we gathered data through a participatory design approach to conceptualize educational games for cat care. This conceptual framework then served as a reference for prototyping educational games focused on cat care. The efficacy of these prototypes was evaluated through tests conducted with five cat lover participants. The resulting educational game prototype demonstrated an average value that effectively met the test objectives. Therefore, it can be concluded that the participatory design approach has the potential to generate an appropriate interaction design suitable for implementation in educational games designed for cat enthusiasts.